Does the Apoptosis Value of Cumulus Cells Play a Role in Rescue Oocyte in Vitro Maturation? - Irez, Tulay; Ercan Dogan, Sinem; Ciraci, Enver; Aksoyer, Saadet Busra; Toprak, Muhammet Sait; Dayioglu, Nurten; Guralp, Onur (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: In this study, we aimed to investigate the role of the cumulus cell’s apoptosis parameter in the maturation of immature rescue oocytes. STUDY DESIGN: In this experimental study, donated immature germinal vesicle oocytes were cultured for, in vitro maturation, embryo development in matured germinal vesicle oocytes were compared with apoptotic properties of cumulus cells. RESULTS: In all of the immature oocytes after oocyte in vitro maturation, the maturation rate has been observed as 56.1% and 2PN rate as 63.0%. Afterin vitro maturation of germinal vesicle oocytes, there was no difference in apoptosis rates of the cumulus cells between mature and immature oocytes (p> 0.05). The ratio of 2PN in matured germinal vesicle oocytes showing embryo development was 35.4%. A positive correlation was found between luteinizing hormone values on day 3 and E2 values during HCG days during oocyte maturation and embryo development (p=0.021, p=0.020). In addition, it has been observed that the germinal vesicle oocytes, which have completed their maturation and developed into embryos, have high E2 values during HCG days (p=0.020). CONCLUSION: In our study, it has been demonstrated that in vitro maturation in rescue oocytes from stimulated cycles, embryo development potential could not be explained by the apoptosis parameter.